An Approach on Nonlocal Neutral Impulsive Fractional Differential Equation of Sobolev Type via Poisson Jumps - Manjula, M.; Kaliraj, K.; Vivin, J. Vernold (Discontinuity, Nonlinearity, and Complexity, 2026)
The present work establishes the neutral fractional impulsive differential equation (NFIDE). The fixed-point method and probability density function (PDF) are used to demonstrate the existence and uniqueness of solutions through nonlocal conditions. We show that the approximation integral equation solutions are convergent to the corresponding integral equation. The convergence is shown using the fractional theory. We then obtain an original solution via the Faedo-Galerkin approximation techniques. Additionally, we provide an application for assessing empirical outcomes.